1997
DOI: 10.1128/jvi.71.12.9813-9816.1997
|View full text |Cite
|
Sign up to set email alerts
|

Efficient neutralization of foot-and-mouth disease virus by monovalent antibody binding

Abstract: Neutralization of an aphthovirus by monovalent binding of an antibody is reported. Foot-and-mouth disease virus (FMDV) clone C-S8c1 was neutralized by monoclonal antibody (MAb) SD6, which was directed to a continuous epitope within a major antigenic site of the G-H loop of capsid protein VP1. On a molar basis, the Fab fragment was at most fivefold less active in neutralization than the intact antibody, and both blocked virus attachment to cells. Neither the antibody nor the Fab fragment caused aggregation of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…This is the first study to investigate the details of the antibody-binding and neutralization mechanisms of parvoviruses. The mechanisms are generally similar to those reported for the neutralization of other nonenveloped and enveloped viruses, indicating that there are only a limited number of processes of neutralization for most viruses (Outlaw and Dimmock, 1991;Smith, 1993;Verdaguer et al, 1997;Che et al, 1998;Fleury et al, 1999;Sattentau et al, 1999;Smith and Baker, 1999).…”
Section: Fig 5 (A)supporting
confidence: 69%
See 1 more Smart Citation
“…This is the first study to investigate the details of the antibody-binding and neutralization mechanisms of parvoviruses. The mechanisms are generally similar to those reported for the neutralization of other nonenveloped and enveloped viruses, indicating that there are only a limited number of processes of neutralization for most viruses (Outlaw and Dimmock, 1991;Smith, 1993;Verdaguer et al, 1997;Che et al, 1998;Fleury et al, 1999;Sattentau et al, 1999;Smith and Baker, 1999).…”
Section: Fig 5 (A)supporting
confidence: 69%
“…The interactions involve antibody binding to the viral structures in a number of different ways, including binding to flexible loops (Logan et al, 1993;Verdaguer et al, 1999) or to structures that are determined by the folded polypeptide (Colman et al, 1987;Malby et al, 1993;Bizebard et al, 1995;Che et al, 1998;Malby et al, 1998). The mechanisms of virus neutralization can include virus aggregation, masking of receptor attachment sites, steric inhibition of receptor binding, or stabilization of the capsid to inhibit virus uncoating (Outlaw and Dimmock, 1991;Smith, 1993;Verdaguer et al, 1997;Fleury et al, 1999;Sattentau et al, 1999;Smith and Baker, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This structure revealed that the RGD triplet participates directly in the interaction with antibody SD6 (52,53). Cryoelectron microscopy (18) and biochemical (51) studies have shown that SD6 is an effective neutralizer that binds monovalently to particles without causing aggregation of virions. Antibody SD6 neutralizes by blocking attachment of virus particles to cells (51).…”
mentioning
confidence: 92%
“…Cryoelectron microscopy (18) and biochemical (51) studies have shown that SD6 is an effective neutralizer that binds monovalently to particles without causing aggregation of virions. Antibody SD6 neutralizes by blocking attachment of virus particles to cells (51). A dual participation of capsid amino acids in receptor recognition and antibody binding has recently been observed also for poliovirus (15) and rhinovirus (47).…”
mentioning
confidence: 99%
“…Antikörper binden spezifisch an Oberflächenantigene von Erregern, um diese zu neutralisieren und als "fremd" zu markieren (Opsonisierung). Die Anhef-tung des Erregers an die Zielzellen und damit dessen Vermehrung wird vermieden und die klinische Manifestation der Erkrankung verhindert (41).…”
Section: Passive Immunisierungunclassified